Adult development aging - Diane E. Papalia...(et al.) (Boston : McGraw-Hill, 2002)
Redesigned and thoroughly updated, Adult Development and Aging clearly and concisely delivers the most current research findings in the field, with a writing style that students and instructors applaud. Using a topical organization, this edition provides a balanced, positive perspective on adult dev
Includes bibliographical reference and index
Keywords: Adulthood Psychological aspects, Aging Psychological aspects, Adulthood